Expected progeny difference for the weaning weight in crossbred heifers selection in Manabí - Carlos Larrea-Izurieta (Revista MVZ Cordoba, 2019)
Objective. Determine the progeny difference expected (DEP) for the weaning weight adjusted to 205 days (PD) in crossbreed Brahman females born in 2016 as selection criteria for future breeders. Materials and methods. It is analyzed 3467 records generated between 1983 and 2016 in the Napo farm (San Vicente, Manabí, Ecuador). The statistical model included the random effect of the father and as fixed effects: breed composition, sex and year of birth. The variance analysis was performed using the GLM procedure of the SAS statistical package. The components of the variance between and within the father to calculate the heritability (h2) of the PD and the breeding values, the MTDFRELM software was used, applying the animal model, through the evaluation system of the Best Linear Unbiased Predictor (BLUP). Results. It was found that the PD average for the 349 females born in 2016 was 173.67±34.23 kg. A highly significant difference (p≤0.01) was found for the random and fixed effects. The h2 for PD was 0.13±0.04. The DEP fluctuated between -6.13 and +5.58 kg with a range between the breeding values of 11.71 kg and an accuracy between 0.50 and 0.72. Conclusion. The low h2 found for PD shows the high influence of non-genetic factors; it is necessary to identify the best crossbreed that adapts to the livestock in order to obtain high performance products in the PD.